EFFECTIVENESS OF RESTRUCTURING PROBLEMATIC PEOPLE'S BUSINESS CREDIT FINANCING AT BSI KCP LUBUK SIKAPING - Putri Rizkika Handayani; Rini Elvira; Gusrianti; M. Imamuddin (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
One of the activities of Islamic banks is financing. The People's Business Credit (KUR) product is one of the products owned by BSI KCP Lubuk Sikaping. However, several communities in Lubuk Sikaping experience problematic KUR financing. One way to overcome problematic financing is through financing restructuring. This study aims to observe the implementation of restructuring of problematic KUR financing at BSI KCP Lubuk Sikaping and to observe the effectiveness of the restructuring efforts that have been carried out. This study is a type of research using a descriptive qualitative method with data collection techniques through structured interviews and literature studies. The results of this study indicate that the implementation of restructuring of problematic KUR financing at BSI KCP Lubuk Sikaping goes through several stages: customer applications, document collection, financing analysis, customer interviews, and a committee with decision-makers. In practice, BSI KCP Lubuk Sikaping has been effective in carrying out restructuring efforts